Why do transient ischemic attack patients have higher early stroke recurrence risk than those with ischemic stroke? Influence of patient behavior and other risk factors in the North Dublin Population Stroke Study. Issue 1 (January 2017) - Akijian, Layan; Ní Chróinín, Danielle; Callaly, Elizabeth; Hannon, Niamh; Marnane, Michael; Merwick, Áine; Sheehan, Órla; Hayden, Derek; Horgan, Gillian; Duggan, Joseph; Kyne, Lorraine; O'Rourke, Killian; et al.
Background: Few studies have directly compared stroke recurrence rates after stroke and transient ischemic attack, and the risk factors underlying early recurrence are poorly understood. We aimed to investigate risk factors for recurrent stroke after first stroke and transient ischemic attack in a population-based study. Methods: The North Dublin Population Stroke Study applied multiple overlapping hot and cold pursuit methods, to ascertain hospital- and community-treated stroke and transient ischemic attack patients over a 12-month period. Inclusion criteria were: (1) Stroke-physician confirmed transient ischemic attack/ischemic stroke; (2) first-stroke/transient ischemic attack event within the ascertainment period. Patients were prospectively followed at 72 h, 7, 28 and 90 days. Results: A total of 584 patients met eligibility criteria (172 transient ischemic attack, 412 stroke). More transient ischemic attack than stroke patients presented to medical attention with recurrent stroke (8.24% vs. 0.24%, p = 0.0002). Recurrent stroke was more common after transient ischemic attack than index stroke at each time-interval (at 72 h, 4.07% vs. 1.23%, p = 0.03; at 90 days, 13.45% vs. 5.72%, p = 0.002). Stroke recurrence at 90 days was also associated with delay seeking medical attention after the index event (OR 3.2, p = 0.001), delayed anti-platelet (OR 2.8, p = 0.001) and statin (OR 2.4, p = 0.009) treatment, carotid stenosis/occlusion (OR 2.4, p = 0.008). On multivariable analysis, transient ischemic attack as index event (adjusted OR 2.3, p = 0.02), delayed statin treatment (OR 2.5, p = 0.02), and carotid stenosis/occlusion (OR 2.4, p = 0.02) were independent predictors of 90-day recurrent stroke. Conclusion: A combination of pathophysiological and behavioral factors was associated with early stroke recurrence risk. Improved public awareness to reduce delays to self-referral for transient ischemic attack symptoms is needed.